Narative Review The Effect of Endorphin Massage and Counter Pressure During Labor On Endorphin Hormone Release - Rizal, Wadratul Jannah; Yulizawati, Yulizawati; Hardisman, Hardisman; Firdawati, Firdawati; Rita, Rauza Sukma (Women, Midwives and Midwifery, 2024)
Background: Labor pain is a subjective experience associated with uterine contractions, stretching of the cervix, and descent of the fetal head. According to the World Health Organization (WHO), every year, 210 million pregnancies occur in the world, and 20 million women experience pain due to childbirth. Of the 2700 mothers giving birth, 30% experienced severe pain, 20% of labor was accompanied by very severe pain, and 15% experienced mild pain. Non-pharmacological therapy continues to be developed in the world of obstetrics, which aims to provide comfort during the birthing process. Endorphin massage and counter pressure are non-pharmacological therapies that can stimulate the release of endorphins and reduce pain and anxiety during childbirth. Objective: This study aims to determine the effect of endorphin massage and counter pressure during labor on the release of endorphin hormones and their benefits. Methods: This research method was a literature review study. Journal searches were carried out by applying online databases such as PubMed, Garuda Portal, ScienceDirect, and Google Scholar. Articles were selected based on inclusion and exclusion criteria. Results: The analysis was carried out on 32 research articles. It was found that endorphin massage and counter pressure are non-pharmacological techniques to overcome and reduce labor pain and anxiety through the help of endorphin hormones which are useful for a smooth delivery process. Conclusion: The influence of endorphin massage and counter pressure during labor on the release of endorphin hormones, which are useful for reducing labor pain, reducing anxiety, increasing comfort, and speeding up the labor process.